ChemInform Abstract: Coupling Biocatalysis and Click Chemistry: One‐Pot Two‐Step Convergent Synthesis of Enantioenriched 1, 2, 3‐Triazole‐Derived Diols. Issue 28 (21st June 2013) - Cuetos, Anibal; Bisogno, Fabricio R.; Lavandera, Ivan; Gotor, Vicente
Abstract A one‐pot synthesis of different enantiopure 1, 2, 3‐triazole‐derived diols (III) and (V) in high yields and excellent enantio‐ and stereoselectivities is achieved under mild conditions in aqueous medium by combining a single alcohol dehydrogenase with a Cu‐catalyzed "Click"‐reaction.